Monitoring and Management of Increased Intracranial Pressure Based on Indonesian Nursing Intervention Standards (SIKI) in Epidural Hemorrhage Due to Mild to Moderate Traumatic Brain Injury: A Case Report - Ridwan Ridwan; Rezeki Nur; Kasmawati Karim (Journal of Holistic Nursing Science, 2023)
Traumatic Brain Injury (TBI) is a serious global health issue that contributes to trauma's high fatality rate. Increased intracranial pressure (ICP) is a serious life-threatening consequence that nurses caring for TBI patients handle regularly. Monitoring and management of increased ICP are nursing interventions included in the Indonesian Nursing Intervention Standards (SIKI) that can be applied in TBI patients to monitor and avoid elevated ICP. In this case, we describe a 12-year-old child with mild to moderate TBI who suffered an epidural hemorrhage as a result of a traffic accident. Nursing care is delivered by concentrating on monitoring interventions and ICP improvement management based on SIKI. Nursing intervention for monitoring and management of increased ICP based on SIKI used on this patient have been shown to avoid worsening of the condition and mortality in epidural hematoma patients with TBI.